Female and Male Differences in Academic Achievement in Individuals With Cleft: A Population-Based Register Study. (February 2018) - Persson, Martin; Becker, Magnus; Conrad, Amy L.; Svensson, Henry
Objective: The focus of this study was to determine if there is any significant difference in academic achievement for girls and boys with a cleft compared to the general population of Swedish students at graduation from compulsory school. Design: A retrospective population-based study using data obtained from the Swedish Medical Birth Register that was linked to the Swedish School–Grade Register. Participants: Two hundred seventy girls and 241 boys with cleft palate (CP), 222 girls and 429 boys with cleft lip (CL), and 299 girls and 531 boys with cleft lip and palate (CLP) were compared with the compulsory school population comprising 609, 397 girls and 640, 007 boys. Main Outcome Measures: (1) Odds of receiving the lowest grade and reduced odds in receiving high grades in Mathematics, English, and Swedish. (2) grade point average (GPA). Results: In all 3 subject grades, for boys with cleft there was no difference when compared to the male population. Girls with cleft were similar to their peers with a few exceptions. Girls with CLP had lower Math grades, and girls with CP had lower Math, English, and Swedish grades. Girls with CP and CLP achieved a significantly lower GPA in comparison to the female population and boys with CP and CL achieved lower GPAs in comparison to the male population. Conclusions: This study indicates that educational outcomes for girls with cleft are more negatively affected than for boys with cleft.